Pengaruh Permintaan dan Penawaran Agregat Dalam Perspektif Tawhidi String Relation (TSR) - Yudi Y; Randa Fajar Saputra; Mahyarni M; Nanda Suriadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines aggregate demand and supply from an Islamic economic perspective, grounded in the principles of tawhid and maqasid shariah. Demand is directed toward fulfilling halal needs, while supply emphasizes the production of halal and thayyib goods and services. Zakat policy serves as a crucial instrument for wealth redistribution and reducing social inequality. Additionally, ethical consumption principles encourage moderation in spending to prevent waste and support sustainability. By integrating tawhid values, this concept offers a holistic approach to fostering economic justice, social welfare, and environmental preservation.